2013
DOI: 10.1093/arclin/act073
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Validity and Neuropsychological Assessment: A Survey of Practices and Beliefs of Neuropsychologists in Six European Countries

Abstract: During the last decades, symptom validity has become an important topic in the neuropsychological and psychiatric literature with respect to how it relates to malingering, factitious disorder, and somatoform complaints. We conducted a survey among neuropsychologists (N = 515) from six European countries (Germany, Italy, Denmark, Finland, Norway, and the Netherlands). We queried the respondents about the tools they used to evaluate symptom credibility in clinical and forensic assessments and other issues relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 34 publications
2
48
0
6
Order By: Relevance
“…In line with previous survey findings ( Dandachi-FitzGerald et al, 2013), the majority of neuropsychologists reported that prior to participation in this study, they did not administer SVTs and/or PVTs routinely in clinical assessments. Rather, they added response validity tests to their test battery when certain features were present.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with previous survey findings ( Dandachi-FitzGerald et al, 2013), the majority of neuropsychologists reported that prior to participation in this study, they did not administer SVTs and/or PVTs routinely in clinical assessments. Rather, they added response validity tests to their test battery when certain features were present.…”
Section: Discussionsupporting
confidence: 86%
“…This is an important question whenever response validity tests are not incorporated in test batteries per default. In a recent survey among European neuropsychologists (Dandachi-FitzGerald, Merten, & Ponds, 2013), only 12% of the respondents indicated that they included response validity tests in every or nearly every clinical neuropsychological assessment. Thus, many European neuropsychologists will be regularly confronted with the question of whether or not they should add response validity tests to their test battery.…”
mentioning
confidence: 99%
“…Respecto a los diseños de grupos mixtos, cabe destacar su escasa utilización en la investigación del constructo (Santamaría Fernández, 2014), debido a que los estudios llevados a cabo con estrategias de grupos conocidos y con muestras análogas, o con la estrategia combinada de éstas dos metodologías han demostrado la mayor fiabilidad en la investigación de la simulación (Rogers, 2008b;Rogers y Bender, 2003). Sin embargo, la validación empírica de la simulación se ha visto limitada porque la mayoría de porcentajes estimados de simulación se ha obtenido también a partir de muestras homogéneas y análogas (Dandachi-FitzGerald et al, 2013).…”
Section: P á G I N Aunclassified
“…Dentro de los resultados obtenidos se ha estimado una prevalencia de simulación del (9.7%), esta incidencia de simulación está en la línea de las evidenciadas en la práctica general, estimadas en un (7%) (Dandachi-FitzGerald, Ponds, y Merten, 2013). Si bien, los sujetos clasificados como indeterminados en la condición de simulación en esta tesis, presentan resultados para todos los análisis efectuados, estadísticamente análogos a los obtenidos por aquellos sujetos probablemente simuladores.…”
Section: Discusión Generalunclassified
See 1 more Smart Citation